William Michael Schmidli, The fate of freedom elsewhere. Human rights and U.S. Cold War policy, Ithaca, Cornell University Press, 2013, 272 páginas - Carassai, Sebastián (2016)
Fil: Carassai, Sebastián. Universidad Nacional de Quilmes. Centro de Historia Intelectual; Argentina.